PENGARUH PAJAK HOTEL, PDRB, TINGKAT HUNIAN HOTEL, JUMLAH WISATAWAN, COVID-19 TERHADAP PAD - Jomaki, Tiara Rachellya Chrisanta; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2023)
The regional autonomy system that has been in effect in Indonesia since 1999 has given each region the freedom to organize and manage its own government affairs, including regional financial affairs. Malang Raya, which consists of 3 regions, namely Malang City, Batu City, and Malang Regency has enormous tourism potential to increase PAD. The purpose of this study was to determine the effect of hotel taxes, the GRDP of the accommodation and food and drink provider sector, hotel occupancy rates, the number of tourists, and the COVID-19 pandemic on PAD in Malang Raya. This study uses a descriptive quantitative method using secondary data obtained through the Central Bureau of Statistics in the three regions of Greater Malang. The analysis technique of this research was done by using panel data regression. Based on the results of this study, the results of the food and beverage GRDP, hotel occupancy rates, and the number of tourists partially had a positive and significant effect on PAD, while hotel taxes had a negative and significant effect on PAD, and the COVID-19 pandemic resulted in a decrease in PAD in 2020. However, in terms of Simultaneously, hotel taxes, food and beverage GRDP, hotel occupancy rates, the number of tourists, and the Covid-19 pandemic have an effect on PAD.